Atividade gastroprotetora de Combretum duarteanum Cambess. (Combretaceae) em modelos animais - Lima, Gedson Rodrigues de Morais (2011)
Combretum duarteanum Cambess is popularly known as mofumbo, a unique species from Latin America, usually associated with arid environments. This species belongs to Combretaceae family, known in various continents of the world for its popular use in treatment of inflammation and infections, its effects are usually associated with its major constituents, flavonoids, tannins and terpenes. The crude ethanol extract (Cd-EtOHE) and the hexane phase (Cd-HexP) obtained from the leaves of C. duarteanum Cambess were evaluated for toxicity and pharmacological effects against gastroprotective activity and healing, as well as the likely mechanisms of related actions. Oral administration (p.o.) 2000 mg/Kg of Cd-EtOHE, in mice did not show behavioral changes. Regarding water intake, was observed that the extract did not cause significant changes in both the groups, both in males and in females. However the feed intake was observed to decrease significantly in the group of males treated. No animal died and no significant macroscopic changes in daily body or organ weight were observed, making it impossible to determine the LD50. The Cd-EtOHE and Cd-HexP were assessed for their gastroprotective activity in models of acute ulcer induced by HCl/ ethanol, absolute ethanol, stress (immobilization and cold), nonsteroidal anti-inflammatory drug (piroxicam) at doses with 62.5, 125, 250 and 500 mg / kg (p.o.) and pylorus ligature (250 mg/kg v.o. and i.d.) in Swiss mice and male Wistar rats. In the model HCl / ethanol, Cd-EtOHE (62.5 125, 250 and 500 mg / kg, p.o.) significantly reduced the ULI the ulcerative lesion index in 28, 36, 55 and 63% respectively. It was also observed in the ethanol model Cd-EtOHE and Cd-HexP (62.5 125, 250 and 500 mg/kg, p.o.) significantly inhibited the ULI in 51, 48, 61, 45 and 37, 44, 79, 86 %, respectively. In the stress model Cd-EtOHE (125, 250 and 500 mg / kg, po) reduced the ULI in 44, 54 and 69% and Cd-HexP (62.5, 125, 250 and 500 mg / kg po) was about 55, 56, 69 and 79%.In the NSAID-induced ulcers, the percentages of protection for Cd-EtOHE (125, 250 and 500 mg / kg, po) and Cd-HexP (250 and 500 mg / kg, po) were 30, 42, 49 and 43%, 52% , respectively. The results obtained front of the restraint of gastric secretion (pylorus ligation) have shown that Cd-EtOHE (250 mg/kg) or Cd-HexP (250 mg/kg), showed protection both given orally (p.o.) (66 and 39%) or by intraduodenal route (i.d.) (41 and 45%), respectively. The data showed that the Cd-EtOHE and Cd-HexP, did not promote changes in pH and the volume of gastric juice. To evaluate the gastroprotective activity and the likely mechanisms of related actions of the Cd-EtOHE (250 mg / kg) and Cd-HexP (250 mg / kg) were carried out experimental protocols to assess the contribution of mucus, nitric oxide and sulfhydryl groups. According to the obtained results, it is possible to suggest that the gastroprotective effect does not include the mucus participation, but is dependent on the nitric oxide and sulfhydryl compounds participation. In the model of acetic acid induced ulcer, chronic treatment with Cd-EtOHE (250 mg / kg, po) and Cd-HexP (250 mg / kg, p.o.) significantly reduced the ulcerative area in 38 and 48%, respectively. During the 14 days of treatment, we observed that the Cd-EtOHE increased the water and food intake, but for Cd-HexP this effect was not observed. These results suggest that the Cd-EtOHE and Cd-HexP displays gastroprotective activity, which are related the participation of NO, an increase in endogenous SH compounds, as well as the growth factors involvement in the healing process induced by the chemical constituents present in the vegetable samples tested.